Rapid Processing and Scanning Electrochemical Techniques Applied to Sintered Nickel Electrodes of Varying Thickness and Rate Capability. (10th February 2015) - Mabbett, Ian; Marinaccio, Jordan; Glover, Carol; Barnes, A; Subramanian, R; Williams, Geraint; Worsley, David A
Abstract : Nickel based battery chemistries still have a place in stationary energy storage applications such as in back up accumulator storage for photovoltaic devices, owing to the long lifetimes and relative safety of these technologies. In this study rapid Near Infrared (NIR) radiative heating is used to sinter electrode pastes into plaques in 10's of seconds as opposed to 10's of minutes via traditional convection sintering routes. This step change reduction in processing time is useful in enabling rapid roll-to-roll manufacture of large-scale electrodes. In order to avoid difficulties associated with controlled atmospheres, reducing agents were added to the electrode pastes. Sintered plaques were characterized using typical physical techniques such as SEM/EDX, XRD and BET but scanning electrochemical techniques, more typical in corrosion studies, have also been used to investigate current densities and spatially resolved surface potential maps and identify how regions of varying thickness effect rate capability.